Health Financing and its Effect on the Equity of Healthcare Systems and Universal Coverage in Sub-Saharan Africa - Okaka, Damianus Ochieng (University of the Witwatersrand, Johannesburg, 2023)
This work examines the contribution of different arrangements for financing healthcare to health systems’ equity in Sub-Saharan Africa (SSA); with equity of the health system measured as health outcomes. More specifically, the study explores: 1) How financing of healthcare using domestic resources affects health outcomes. The effect of increased budgetary allocation to healthcare on health outcomes. And the effect of financial pooling and financial risk mitigation on the health systems’ equity. The concept of health production, based on Grossman’s (1972 & 2017) health capital theory, serves as the framework for empirical analysis of this work, using balanced panel data from 47 SSA countries, over 19 years. The dataset is pulled from relevant governments’ and multi-lateral organizations’ databases. Broadly, descriptive statistics and multivariate regression analysis are deployed in assessing the hypothesized relationships between the study’s relevant variables – financing of countries’ healthcare systems and various forms of health outcomes (i.e., life expectancy at birth, 5-year mortality rate, crude death mortality rate, and rate of infant mortality). The results indicate that financing healthcare using domestic public resources does relate insignificantly or negatively to health outcomes, but financing healthcare using domestic private resources relates significantly well with health outcomes. An increase in budgetary allocation to healthcare per capita relates beneficially to health outcomes. However, an increase in budgetary allocation as a percentage of total government expenditure affects the region’s health outcomes adversely; however, further tests of this relationship reveal that a reduction in indirect investment in healthcare could be responsible for the adverse effects. Thus, pointing to the need to balance the effects of the increase in both direct and indirect healthcare investments (expenditures). Lastly, apart from financial pooling using the private health insurance method, which affects health outcomes negatively, all the other pooling methods of healthcare financing affect the region’s health outcomes favorably. However, the social health insurance (SHI) effect on the region’s health outcomes is largely insignificant. Which may call into question its appropriateness as a vehicle for universal health coverage (UHC). The main conclusion of the study is that governments’ participation in healthcare financing is necessary for the SSA region’s health systems. However, increased government allocation should not be done at the expense of allocation to health-related activities (like the provision of clean water, sanitary services, etc.). We also found that domestic private healthcare funding methods associate favorably with health outcomes while domestic public healthcare funds do not. We argue that the reason for these confounding results is because of allocation problems, and recommend redistributive policies with a focus on the indigent and rural areas. Further diagnostic tests show that domestic public financing methods increase access to healthcare but not health outcomes. This shows that a financing method can increase access to healthcare but fail to improve population health status. Our findings also show that SSA health systems still need external financial assistance to be equitable. We recommend a gradual weaning from external assistance. On risk pooling, we recommend an increase in pool sizes and more accurate actuarial data to improve the performance of SHI and, to make it appropriate for UHC. Finally, governments of the SSA region should increase funding of healthcare by using public resources, ensure healthcare financing risk mitigation by increasing pool sizes of public financial pooling methods, and enact requisite legal and regulatory frameworks to guide the administration of private non-profit healthcare finance pooling schemes. Importantly, these governments should consider policies that correct for imbalances in the distribution of healthcare between the rich and the poor, and between rural and urban areas
A research report submitted in partial fulfillment of the requirements for the degree of Doctor of Business Management to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Healthcare; Equity; Universal coverage; Healthcare financing; Financial pooling; Utility; Social welfare; UCTD; SDG-8: Decent work and economic growth